Pengaruh Corporate Governance dan Diversifikasi terhadap Kinerja Keuangan Perusahaan yang Menerapkan Enterprise Resource Planning (ERP) - Nazhfiyani KS; Rita Rahayu; Rayna Kartika (Universitas Batanghari Jambi, 2022)
This study aims to prove empirically the effect of corporate governance and diversification on the financial performance of companies that have implemented enterprise resource planning. The dependent variable in this study is financial performance as measured by Return On Assets. The independent variables in this study are corporate governance and diversification. Corporate governance is measured by the proportion of the independent board of commissioners. Diversification is measured by the number of business lines. This study uses firm size as a control variable. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange. Based on the purposive sampling method, the samples obtained were 33 manufacturing companies that met the criteria. The analytical method used is multiple linear regression analysis with SPSS software version 25. The results showed that corporate governance has a positive effect on the financial performance of manufacturing companies that have implemented enterprise resource planning, and diversification also has a positive effect on the financial performance of companies that have implemented enterprise resource planning.